1967
DOI: 10.1002/cber.19671000423
|View full text |Cite
|
Sign up to set email alerts
|

Anionoradikale, IV. Über radikalische und nicht‐radikalische Alkalimetalladdukte aromatischer Azoxyverbindungen

Abstract: Anionoradikale, lV1) uber radikalische und nicht-radikalische Alkalimetalladdukte aromatischer Azoxyverbindungen rn Beim Schiitteln rnit feinverteiltem Natrium in inerten wasserfreien Losungsmitteln bilden cisund trans-Azoxybenzoldie cis-Verbindung rascherein blaues, radikalisches Mononatriumaddukt, das bei langerer Einwirkung von Natrium in ein braunrotes, nicht-radikalisches Dinatriumaddukt iibergeht. Wasser hydrolysiert sowohl das Monoals auch das Dinatriumaddukt zu Azobenzol; im Falle des Mononatriumaddukt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
1975
1975

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It was observed that the initially formed radical anion intermediate does not undergo further reaction and the starting material was recovered unchanged in appreciable yields, on work-up. However, the reaction of 26 with sodium in tetrahydrofuran resulted in the cleavage of this molecule, and a small quantity of 2-nitrophenol (28) was isolated from this run.…”
Section: Scheme IVmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the initially formed radical anion intermediate does not undergo further reaction and the starting material was recovered unchanged in appreciable yields, on work-up. However, the reaction of 26 with sodium in tetrahydrofuran resulted in the cleavage of this molecule, and a small quantity of 2-nitrophenol (28) was isolated from this run.…”
Section: Scheme IVmentioning
confidence: 99%
“…-Acylation of Metal Enolatesla Herbert 0. House,* Robert A. Auerbach, Martin Gall,111 and Norton P. Peet School of Chemistry, Georgia Institute of Technology, Atlanta, Georgia 30882 Received August 28, 1972 From a spectroscopic examination of metal enolates, the mercury(II) salts of ketones are found to exist as a-…”
mentioning
confidence: 99%